A comprehensive assessment of low-temperature preheating process in natural gas pressure reduction stations to better benefit from solar energy. (15th October 2020) - Olfati, Mohammad; Bahiraei, Mehdi; Nazari, Saeed; Veysi, Farzad
Abstract: In this study, a thermodynamic model is developed for a natural gas pressure reduction station, which uses solar energy as an auxiliary energy source for preheating the natural gas. To increase the duration of solar energy usage per day and the consequent decrease in the fuel consumption of the heater, a novel design is presented in which preheating the gas to lower temperatures becomes possible through the use of multi-stage preheating and pressure reduction. Through this novel design, it becomes possible to utilize a single heater to preheat all stages, which reduces the costs dramatically. To investigate the effectiveness of the proposed design in different climate conditions, a comprehensive economic analysis is conducted based on fuel saving and carbon dioxide emission reduction. The results show that the return of capital is within 1–10 years considering different parameters, including: 1- daily time duration of solar energy usage by the station before implementation of the new design, 2- additional daily time duration of solar energy usage after implementation of the new design, and 3- number of preheating and pressure reduction stages. Finally, the effects of different parameters on the return of capital are discussed. Highlights: Natural gas pressure reduction station with solar energy as an auxiliary source. Demand side management to reach low-temperature heating. Multi-stage preheating and pressure reduction design. Annual saved fuel and reduction of CO2 emission. Return of capital depending on climate condition and station inlet pressure.